Linear Quadratic Control for Temperature Regulation of Solar Herb Drying System - Salehin, Nur Suhadah; A.Jalil, Mohd Hafiz; Hamdan, Rohaiza; Amron, Aqilaa Silmi; Ngadengon, Rafidah (Evolution in Electrical and Electronic Engineering, 2021)
Temperature regulation plays an important role to maintain product quality and the efficiency of the herb drying system. Therefore, this paper focuses on the implementation of Linear Quadratic Regulator (LQR) controller for temperature regulation of solar herb drying systems. The simulation result indicated that LQR is capable to provide better performance compared with PID controllers in regulating the temperature of the herb drying system. On the other hand, the result also shows that LQR is capable to prevent the response from overshoot and produce 82% faster settling time as compared with PID.